2018
DOI: 10.1097/ta.0000000000001937
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of emergency department thoracotomy in a statewide trauma system: Does center volume matter?

Abstract: Prognostic/Epidemiological, level III; Therapeutic, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
15
1
2
Order By: Relevance
“…Dumas et al found evidence for other surgical disciplines and procedures. For example, they found advantageous outcomes of tracheotomies as small, routine, emergency procedures at HVCs [ 51 ]. Amato et al found advantages for HVCs for 26 clinical areas, including hip fractures [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dumas et al found evidence for other surgical disciplines and procedures. For example, they found advantageous outcomes of tracheotomies as small, routine, emergency procedures at HVCs [ 51 ]. Amato et al found advantages for HVCs for 26 clinical areas, including hip fractures [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 18 19 ] A recent study in a single state by Dumas et al . [ 7 ] found that patients presenting to centers that had a higher mean annual volume of EDTs performed had significantly higher odds of survival. Unfortunately, we are restricted by the HCUP policies on reporting data with <10 observations and are unable to report the survival among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although urban institutions overall perform a higher volume of EDTs, evidence has not shown that teaching status has a significant effect on patient outcomes from EDT. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First responders usually lack the clinical experience necessary for treating complex patients, let alone in stressful situations 1. When lifesaving interventions are due, level of experience is yet another key factor impacting procedure success rate 2–4…”
Section: Introductionmentioning
confidence: 99%